Mengurai Pengalaman Positif Tamu Saat Menginap di Sheraton Senggigi Beach Resort: Bukti Dari Ulasan TripAdvisor - Ahmat Setiawan; Febrian Humaidi Sukmana (Ministry of Tourism and Creative Economy/Tourism and Creative Economy Agency Republic of Indonesia, 2023)
Customer reviews on the internet play an essential role in generating opinions in electronic Word-of-Mouth (eWOM); This review serves as an online communication tool that significantly influences the perception of the following potential user. The purpose of this study is to understand the opinions that often appear in actual customer reviews that give an Excellent and Very Good rating. This study collected 1.515 online review data from the Tripadvisor website using automated web data mining techniques. Next, we used the JMP Pro 14 software to parse and visualize the research data at the analysis stage. The data shows that the most critical customer satisfaction lies in non-physical services, namely